Reliability of kinetic variables of squat jumps with different starting positions - Menzel, H. J.; Pereira de Andrade, A. G.; Ribeiro Araújo, S.; Heleno Chagas, M. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The aims of the study were to compare dynamic variables (impulse, peak force, peak power and rate of force development) derived from squat jumps starting from self-selected and 90 degree knee angles as well as determining the reliability of these variables in the two conditions. Fourteen male junior volleyball players performed three Squat Jumps on a force platform while starting from each position. Intraclass Correlation Coefficients were calculated and t-tests were used to identify differences between the starting positions. In both conditions, most variables showed ICC coefficients greater than 0.85 and no significant differences between the starting conditions were found. It can be concluded that both conditions lead to reliable dynamic data without significant differences and therefore standardized knee angle is not necessary.